Performance Criteria And Utilization Of Performance Appraisal In The Royal Malaysian Police Force - Lee, Yen Thing (1994)
Performance appraisal has become increasingly important tool for organization to use in managing and improving employee' s performance.However,little empirical result has been conducted to determine( a ) the extent to which performance criteria were being selected for performance appraisal,( b ) the extent to which performance appraisal is used for each of several purpose sin the organization,( c ) the extent to which appraisal data maybe used for multiple and possibly conflicting uses within the organization,and ( d ) the psychometric criteria of the new performance appraisal under the New Remuneration System. A survey questionnaire designed to answer these questions was distributed personally to 100 police officers ranking from P/lnsp.to Deputy Superintendent of Police (DSP )in the Special Branch Department ,Bukit Aman,Kuala Lumpur.A correlational and simple Analysis of Variance were utilized to analyze the data of seventy-six completed questionnaires. The findings showed that loyalty,conduct, decision making ability and quality of work were cited among the most important performance criteria,while non-work related activities,adapt ability to work and quantity of work were cited as the least importan